2018
DOI: 10.4103/ijccm.ijccm_394_17
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter observational study to evaluate epidemiology and resistance patterns of common intensive care unit-infections

Abstract: Background:There is limited data regarding the microbiology of Intensive Care Unit (ICU)-acquired infections, such as ventilator-associated pneumonia (VAP), catheter-associated urinary tract infections (CAUTI), and catheter-related bloodstream infections (CRBSI) from India.Objectives:To explore the microbiology and resistance patterns of ICU-acquired infections and evaluate their outcomes.Materials and Methods:This was a multicenter observational study, conducted by Indian Society of Critical Care Medicine (MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 15 publications
1
18
1
Order By: Relevance
“…Among these, one-half only evaluated inhospital outcomes including two studies that restricted to intensive care unit (ICU) outcome alone16,17 with the other three limited to inhospital death 1820. The other one-half of studies evaluated 30-day,21,22 90-day,23,24 and 6-month25 all-cause deaths. We chose BSI to study this issue as a matter of convenience as we had ready access to a detailed population-based database.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, one-half only evaluated inhospital outcomes including two studies that restricted to intensive care unit (ICU) outcome alone16,17 with the other three limited to inhospital death 1820. The other one-half of studies evaluated 30-day,21,22 90-day,23,24 and 6-month25 all-cause deaths. We chose BSI to study this issue as a matter of convenience as we had ready access to a detailed population-based database.…”
Section: Discussionmentioning
confidence: 99%
“…Patients admitted to the medical intensive care unit (MICU) of tertiary referral centers are critically ill and incidences of nosocomial infections are also very high. [ 1 2 ] Antibacterial agents are the most prescribed drugs for rapid control of serious infections to reduce the mortality and morbidity. [ 2 3 4 ] The burden of bacterial disease in India is among highest in the world and the inappropriate use of antibacterial agents leads to increase the development of antibacterial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 3 4 ] The burden of bacterial disease in India is among highest in the world and the inappropriate use of antibacterial agents leads to increase the development of antibacterial resistance. [ 1 5 6 ] Antibiotic resistance has been a low-priority area in most developing and many developed countries. To overcome the burden of infectious disease and rising antibiotic resistance prevalence in India, the Global Antibiotic Resistance Partnership-India Working Group have recommended important interventions which include surveillance of antibiotic use, distributing standard treatment guidelines, increasing the use of diagnostics tests, infection control interventions, educational approaches, and improving antibiotic supply chain and quality.…”
Section: Introductionmentioning
confidence: 99%
“…We observed a predominance of Gram-negative pathogens (92% of 323 culture-positive isolates) in our study, which is different from what is reported from western studies. 10 11 The spectrum of microorganisms responsible for infections in medical ICUs and wards has been reported to be different in western world in comparison to Indian subcontinent. 12 13 The reason for the same is not fully known, albeit, some believe that this may be due to difference in the climatic condition.…”
Section: Discussionmentioning
confidence: 99%